2020
DOI: 10.1111/jpn.13338
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary amylose/amylopectin ratio and amylase on growth performance, energy and starch digestibility, and digestive enzymes in broilers

Abstract: Aims and scopeThe Journal of Animal Physiology and Animal Nutrition publishes original papers on hypothesis-driven research in the fields of animal physiology, physiology and biochemistry of nutrition, animal nutrition, feed technology, and feed preservation but not manuscripts presenting fish (or other aquatic non-mammals) nutritional or growth topics. The journal is a forum for presenting articles on basic and applied research, thus making new findings, methods, and techniques easily accessible and applicabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 32 publications
(30 reference statements)
2
11
1
Order By: Relevance
“…The activity of digestive enzymes is an important factor affecting growth performance [34] yet the current results showed no influence of adding AT, BA, AL-L, AL-H or BA+AL-H on the jejunal mucosal activities of pepsin, trypsin, chymotrypsin or amylase. Similarly, the jejunal trypsin, amylase or lipase were not altered significantly by acidifier [4].…”
Section: Discussioncontrasting
confidence: 71%
See 1 more Smart Citation
“…The activity of digestive enzymes is an important factor affecting growth performance [34] yet the current results showed no influence of adding AT, BA, AL-L, AL-H or BA+AL-H on the jejunal mucosal activities of pepsin, trypsin, chymotrypsin or amylase. Similarly, the jejunal trypsin, amylase or lipase were not altered significantly by acidifier [4].…”
Section: Discussioncontrasting
confidence: 71%
“…As for the addition of AL, Jiang et al found that 750 and 2250 mg/kg AL significantly increased the activities of intestinal AL, protease and trpsin [ 35 ]. Ma et al observed that dietary amylase (3000 and 6000 U/kg) could significantly increase AL activity compared with non-amylase diets [ 34 ]. Therefore, as far as we are concerned, the data on the endogenous digestive enzymes may differ from the dosage and activity of exogenous AL used.…”
Section: Discussionmentioning
confidence: 99%
“…This study showed that when ducks were fed high amylose-corn diets, they tend to have lower TME than those fed low amylose corn. In addition, Ma et al. (2020) reported that AM:AP higher than 0.35 reduced starch digestibility.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, high drying temperatures may promote the occurrence of Maillard reactions ( Žilić et al., 2013 ), leading to poor digestibility of some essential amino acids, especially lysine ( Wall and Donaldson, 1975 ; Rutherfurd et al., 1997 ; Odjo et al., 2015 ), cysteine, tyrosine, and threonine ( Kaczmarek et al., 2014a ). Endosperm hardness may play an important role in animal responses due to variations in starch structure, the content of resistant and damaged starch, amylose and amylopectin ratio, and the physical fragmentation properties during grinding that can influence feed traits, gut development and morphology, and ingestion behavior ( Kaczmarek et al., 2014a ; Córdova-Noboa et al., 2021 ; Ma et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…The starch content may also be one of the factors affecting the digestibility. The starch source and amylose/pullulan ratio all affect the digestibility of starch and other nutrients in animals [ 46 ]. Starches from different grains also respond differently to enzymes.…”
Section: Discussionmentioning
confidence: 99%